INTERNALISASI NILAI-NILAI SPIRITUAL PADA DIRI SISWA DI SMPN 2 KOTA BENGKULU - Ediyono Ediyono (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2018)
This research  describes the condition of students’ spiritual attitudes,  methods used by Master and the constraints and support  of the internalization process  of spiritual value itself. This research  used qualitative  descriptive  and  interactive  method with observation, documentation, observation and interview. The result of the research  is that before the internalization of these spiritual values,  the condition of understanding and  religious practice  is still far from being expected. Meanwhile,  after the in- ternalization  is performed, the result of difference is increase  the awareness of students  to implement  and practice the worship, especially mandatory prayer  in congregation. Morals and  behaviors are increase  and  the respect  for teachers  also increase  so that  this affects the increase  in student  achievement itself. Methods  used  include  Teacher  Role Improvement Method,  Guid- ance  and  Counseling Method,  Tauladan Method,  Cultural  Method,  and  Tabligh Method.  While the inhibiting  factors are  the background of family conditions  and the limited role of teachers  in conducting guidance and learning.  The supporting factor is the application of K-13 curriculum  which is very compatible with the activities of spiritual values in the students.  The teachers awareness in giving tauladan to their students  also increase